Geomorphological characteristics of the Wabash River, USA: Influence on fish assemblages. Issue 9 (18th March 2021) - Robbins, Jeff; Pyron, Mark
Abstract: River hydrogeomorphology is a potential predictor of ecosystem and assemblage variation. We tested for fish assemblage variation as a function of hydrogeomorphology in a Midwestern US large river, the Wabash River. Fish data were classified by taxonomy and traits and we tested if assemblages varied with river hydrogeomorphology or river distance, defined into 10‐km distinct reaches. Three unique geomorphological units, Functional Process Zones (FPZ), were identified using an ArcGIS hydrogeomorphic model, based primarily on channel width, floodplain width, and down valley slope. Five locations were identified as FPZ A with narrow stream channel, high down valley slope, and an expansive floodplain. Ten locations were identified as FPZ B with a wide river channel and wide floodplain. Thirty‐five locations were identified as FPZ C with wide river channel and a constrained floodplain. The sites were categorized into three stream orders: 5, 6, and 7. We found hydrogeomorphology classified by unique FPZs or by river distance influenced taxonomic and functional fish assemblages for the Wabash River. There was high overlap among fish occurrences among FPZs, but nine species resulted as significant indicators of specific FPZs. Five traits were significant indicators of FPZs: an intermediate Swim Factor score, medium tolerance to silt, small‐large stream size preference, and two Shape Factor categories. Our conclusions are that fish assemblages respond strongly to local geomorphology and river distance, fitting the riverine ecosystem synthesis and the river continuum concept. Abstract : We tested for fish assemblage variation as a function of hydrogeomorphology in a Midwestern US large river, the Wabash River. Fish data were classified by taxonomy and traits and we tested if assemblages varied with river hydrogeomorphology or river distance, defined into 10‐km distinct reaches. Our conclusions are that fish assemblages respond strongly to local geomorphology and river distance, fitting the riverine ecosystem synthesis and the river continuum concept.